Pengaruh acid wash cell elektrolyzer terhadap kenaikan nilai k faktor pada unit chemical making 13 PT. Indah Kiat Pulp and Paper tbk. Perawang – Riau - Fithry , Dwi Annisa; Rawadi, MHD Raihan; Yusri, Muhammad; Azhar, Helmi; Siburian, Sutoyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Sodium chlorate (NaClO3) is used to produce clorine dioxide (ClO2), which is used in the bleaching process in the pulp and paper industry. Sodium chlorate is produced in the industry by electrolysis process. This electrolysis process produces 2 main products, namely hydrogen and sodium chlorate. hydrogen is used in the process of making hydroclorid acid (HCl) and sodium chlorate is used in the process of making ClO2. In the process of making chlorate there are several things that must be considered, including: pH, oxygen levels in the degasifier, conditions of the hypo tower system, salt and chlorate concentration, and K cell factor. Based on the results of the above analysis, it can be seen that the acid wash cell is able to reduce the K factor of the cell. Do not run the electrolyzer if the cell voltage is above 3.5 volts. This is because at a voltage above 3.5 volts oxygen formation occurs, if oxygen meets hydrogen gas from electrolysis can cause an explosion.